The role of Islam and natural resources in current Mali political turmoil - Shuriye, Abdi Omar; Ibrahim , Dauda Sh. (MCSER-CEMAS-Sapienza University of Rome, 2013)
In the recent times, the Republic of Mali has been striving to restore peace and harmony in the state. The conflict initiated by insurgent Islamist groups fighting against the Malian government for independence in northern Mali. The revolt against the government is associated with the implementation of shariah laws. Despite the current decrepit political condition in Mali it seems to be a site of attraction of Western military intervention. This paper studies the role of religion and natural resources in the conflict. Mali is one of the poorest countries in the world but in reserve it has one of the largest amounts of mineral deposits including uranium and other energy related resources. The significance of this paper is that it critically analyses the legality, motives and purpose of French intervention in Malian conflict and direct US support for it.